“So, Obama is a Muslim?”: toward figurative spaces and blends in US same-sex marriage discourse - Pongbodin Amarinthnukrowh, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This article investigates the meaning construction processes of novel figurative expressions found in the discourse on the US legalisation of same-sex marriage. It is argued that mental spaces theory and conceptual blending theory (MSCB) can be of great analytical benefits when dealing with this type of data. Four cases of novel figurative spaces and blends, namely the Divided Self construal, the Generic is Specific construal, the single-scope blending, and the megablending, are examined to shed light on how same-sex marriage controversies are conceptualised by means of the viewpointed nature of figurative language. In addition, based on the analyses of the four selected cases, this article ends with a discussion on why MSCB is an appropriate choice for examining novel figurative expressions in discourse.